2016
DOI: 10.1002/brb3.489
|View full text |Cite
|
Sign up to set email alerts
|

Bone density and depressive disorder: a meta‐analysis

Abstract: BackgroundThe aim of this study was to evaluate the evidence of low bone mineral density (BMD) in depression. Low BMD is a major risk factor for osteoporotic fractures and frailty.MethodsThe searched database was Pubmed, Meta‐analysis included human studies in men and women fulfilling the following criteria: (1) assessment of BMD in the lumbar spine, the femur or the total hip; (2) comparison of BMD between depressed individuals and the healthy control group; (3) measurement of BMD using dual‐energy X‐ray abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 49 publications
2
33
1
1
Order By: Relevance
“…Examination of the independent effect of anxiety disorders on bone mineralization is needed, given their high prevalence, their potential impact on sympathetic nervous system signaling, and their high comorbidity with depressive disorders. Of note, population‐based studies have largely failed to show an association between depression and bone mass . We propose that this may be attributable, at least in part, to the fact that the depression severity scales used in epidemiologic studies are not suited for distinguishing between depression and anxiety disorders.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Examination of the independent effect of anxiety disorders on bone mineralization is needed, given their high prevalence, their potential impact on sympathetic nervous system signaling, and their high comorbidity with depressive disorders. Of note, population‐based studies have largely failed to show an association between depression and bone mass . We propose that this may be attributable, at least in part, to the fact that the depression severity scales used in epidemiologic studies are not suited for distinguishing between depression and anxiety disorders.…”
Section: Discussionmentioning
confidence: 92%
“…Major depressive disorder (MDD) is characterized by depressed mood, anhedonia, neuro‐vegetative symptoms (eg, insomnia, anorexia, fatigue), and cognitive symptoms (eg, concentration difficulty) . MDD is associated with low bone mass, increasing one's lifetime risk for osteoporosis and fractures, as well as medical expenditures . The effects of MDD on bone mass has been attributed to dysregulation of the hypothalamic‐pituitary‐adrenal (HPA) axis, other hormonal abnormalities, autonomic nervous system dysfunction, and subclinical inflammation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research is now emerging to suggest that poor bone health is yet another potential comorbidity 5 6. Both clinically diagnosed unipolar depression and depressive symptoms have been associated with deficits in bone mineral density (BMD) and increases in fracture risk in both men and women across the adult age range,7–10 as has schizophrenia,11 alcohol use12 and eating disorders 13. Furthermore, psychotropic agents commonly used in the treatment of bipolar disorder (antidepressants, antipsychotics and anticonvulsants), have each been shown to be independently detrimental to bone 14–16…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have demonstrated that depression is associated with low bone mineral density, especially in women ( Wu et al, 2009 ; Yirmiya and Bab, 2009 ; Schweiger et al, 2016 ). The osteoprotegerin (OPG)/receptor activator of nuclear factor kB (RANK)/RANK Ligand (RANKL)/pathway contributes to bone formation and resorption.…”
Section: Introductionmentioning
confidence: 99%